Electrical Characterization of Atmospheric Pressure Gaseous Discharge - Kandel, SR; Subedi, DP (Kathmandu University Journal of Science, Engineering and Technology, 2010)
This paper reports the generation of atmospheric pressure gaseous discharge and its electrical characterization. For this purpose, a point-plane electrode system has been fabricated. A high voltage power supply (0-11 kV, 50 Hz) was applied across the electrodes. Discharge was generated with and without the dielectric barrier between the electrodes. The gas discharge was seen as in-homogenous filamentary type discharge without the dielectric. Whereas the filamentary discharge turned into bluish glow when the lower electrode was covered by a dielectric. The current and voltage of the discharge were measured by using a high frequency digital oscilloscope. The power consumed by the discharge was measured from the measured values of current and voltage. A special attention has been paid to investigate the effect of electrode geometry on the nature of the discharge Key words: Gaseous discharge; point-plane electrode; dielectric material; filamentary discharge; current and voltage measurement DOI: 10.3126/kuset.v4i1.2887 Kathmandu University Journal of Science, Engineering and Technology Vol.4, No.1, September 2008, pp 81-85